Isolated MYC cytogenetic abnormalities in diffuse large B-cell lymphoma do not predict an adverse clinical outcome. Issue 11 (2nd November 2015) - Caponetti, Gabriel C.; Dave, Bhavana J.; Perry, Anamarija M.; Smith, Lynette M.; Jain, Smrati; Meyer, Paul N.; Bast, Martin; Bierman, Philip J.; Bociek, Robert G.; Vose, Julie M.; Armitage, James O.; Aoun, Patricia; et al.
Abstract : In this study, we investigated the significance of MYC, BCL2 and BCL6 gene abnormalities in a cohort of 205 diffuse large B-cell lymphoma (DLBCL) patients studied by conventional and/or fluorescence in situ hybridization cytogenetic analysis. Combining these methods, 172 cases (84%) were classified as MYC−, 17 (8%) were MYC+ / BCL2 −/ BCL6−, and 16 (8%) were double/triple-hit lymphomas (i.e. MYC+ / BCL2+, MYC+/BCL6+, or MYC+/BCL2+/BCL6+ ). We found a significant difference in event-free survival (EFS) among the three groups ( p = 0.02), with the double/triple-hit group having the worst EFS. Patients who were MYC+, but BCL2− and BCL6−, had the best EFS. We conclude that patients with MYC+ DLBCL, but without BCL2 or BCL6 abnormalities, do not have a worse outcome when compared to those who are MYC−. However, patients with double/triple-hit DLBCL have a very poor outcome and should be treated with aggressive or novel therapies.